PKM EMPOWERING POSYANDU CADERS IN TRAINING VISUAL STIMULATION IN PRESCHOOL AGE CHILDREN - Oktaviani Cahyaningsih; Dewi Sari Rochmayani (Community : Jurnal Pengabdian Pada Masyarakat, 2024)
Nowadays, being apart from gadgets is impossible, gadget fever doesn't matter according to age, in fact, many children are addicted to it so parents need wise attitudes in using technology [1]. Using gadgets for too long is very dangerous for children's eye health [2]. Eye contact with the gadget automatically reduces the frequency of blinking. As a result, the eyes are dry, sore and painful. Then, the eyes become red and itchy, and the child even feels nauseous and dizzy [3]. About 83 percent of the information humans obtain comes through the eyes. Research data shows that the prevalence of blindness in children is 0.2 – 0.3/1000 children in developed countries and 1.0 -1.5/1000 children in developing countries, including the majority of countries in Asia. Around 85 percent of the causes of blindness can be avoided or prevented, namely 78.6 percent can be treated and 7 percent are preventable causes [4]. Carrying out regular eye examinations on children from the age of 3 -5 years is very important to detect problems in children from the start. Usually, an eye examination is carried out if parents notice early symptoms such as the child having difficulty seeing up close or far away or if there is a family history of eye problems. In fact, eye examinations for children are very important to ensure that the child's eyes are healthy and do not have vision problems that could interfere with school performance and have the potential to further affect the child's health [5]. This service activity was carried out through material presentation lectures, practice of using APE Fun Thinkers, Role Play, discussion, evaluation and mentoring of posyandu cadres with the result that there was an increase in knowledge from posyandu health cadres about the importance of visual stimulation which can help improve the play experience of early childhood in recognizing the surrounding environment carefully and well through the sensors they have.